Tinjauan Yuridis Putusan Hakim Terhadap PermohonanPailit Pada Cv. Citra Jaya(Studi Kasus Putusan No. 06/Pailit/2012/PN.Niaga.Smg) - Pamungkas, Bayu Sidiq, Inayah, S.H, M.H (2016)
This study aims to determine the suitability of the judge's ruling in terms of Act 37 of 2004 on Bankruptcy and to determine the consideration of the judge in determining the verdict on the petition of bankruptcy on the CV. Citra Jaya. The method used in this research study normative legal or doctrinal legal research with this type of research is descriptive. The data source consists of secondary data including legal source of primary, secondary and tertiary, while primary data is related to the issues studied were the Office of the Commercial Court of Semarang District Court. Data were collected by literature study and field study that interview, then analyzed by qualitative analysis. The results showed that the judge's decision with the decision number No.06/Pailit/2012/PN.Niaga.Smg, in compliance as stipulated in Law No. 37 Year 2004 on Suspension of Payment, while the judge in determining the consideration is to look how the process of evidence in the trial conducted by the parties and the evidence based on the facts and the reasons of the parties.